2010
DOI: 10.1111/j.1600-0447.2010.01572.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of cognitive behaviour therapy for psychosis in a routine clinical service

Abstract: The only robust improvement was in depression. Nevertheless, there were further encouraging but modest improvements in both emotional and cognitive variables, in addition to psychotic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 57 publications
5
71
3
Order By: Relevance
“…This idea is supported by studies that compared psychosocial treatment in combination with medication with treatment with medication alone (Pijnenborg et al, 2012). These studies show that that insight improved with medication alone in the early phase of treatment (Guo et al, 2010), but not in chronic samples (Merinder et al, 1999;Peters et al, 2010;Turkington et al,2006;Granholm et al, 2005;Chan et al, 2007Chan et al, , 2009) and by studies finding significant improvement of insight over the first two months of antipsychotic treatment in newly admitted patients (Kim et al, 2011) and in individuals with an at risk mental state treated with aripiprazole for three months (Kobayashi et al, 2009). In line with this, our results show that the effects of medication on illness decreases after the first three months of treatment.…”
Section: Discussionsupporting
confidence: 88%
“…This idea is supported by studies that compared psychosocial treatment in combination with medication with treatment with medication alone (Pijnenborg et al, 2012). These studies show that that insight improved with medication alone in the early phase of treatment (Guo et al, 2010), but not in chronic samples (Merinder et al, 1999;Peters et al, 2010;Turkington et al,2006;Granholm et al, 2005;Chan et al, 2007Chan et al, , 2009) and by studies finding significant improvement of insight over the first two months of antipsychotic treatment in newly admitted patients (Kim et al, 2011) and in individuals with an at risk mental state treated with aripiprazole for three months (Kobayashi et al, 2009). In line with this, our results show that the effects of medication on illness decreases after the first three months of treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Of the 14 psychological treatment trials, nine used a randomised controlled design. All drop-out rates from therapy were below 30%, although two studies had lost more that this proportion of participants by the final follow-up assessment (Addington et al, 2011;Peters et al, 2010).…”
Section: Methodological Characteristicsmentioning
confidence: 99%
“…Indeed the proportion of time spent addressing voices in CBTp trials can be small. 28 Furthermore, while some individual trials that have included voices measures have observed improvements, 29,30 including a recent trial with people not taking antipsychotic mediation, 31 most have been insufficiently powered to be conclusive, due to their small sample sizes 32–34 or delivery of therapy during acute relapse when substantial reductions in symptoms arise from routine care alone. 23,35 Nonetheless, a recent meta-analysis 6 (although limited by combining trials delivered during chronic and acute psychosis, and including trials not directly targeting positive symptoms), observed a significant effect of CBTp on posttreatment voice severity vs any control (Hedge’s g = 0.34, 15 studies).…”
Section: Empirical Findings For Psychological Interventions For Voicesmentioning
confidence: 99%